Space and places in Central and Eastern Europe : historical trends and perspectives of regional development - Horváth, Gyula, 1951- (Regions and cities, 2015)
"Across Europe there is a rapidly changing context for undertaking regional development. In the 20th century, development of the former planned economies (Bulgaria, Czech Republic, Hungary, Poland, Romania and Slovakia), was defined by these countries differences, rather than their common ideological roots. These disparities altered over time and were marked by changing social structures. However, the ranking of regions has remained the same as core areas have strengthened their positions while the structural obstacles to the modernisation of peripheral areas have remained due to a lack of coherent regional policy. This book examines the specific regional development paths of Central and Eastern European countries and evaluates the effects of the determining factors of this process. Through analysis of the system of objectives, instruments and institutions used in different eras, and case studies of Hungary, East Germany and Germany, development models are established and compared with Western European patterns. The book summarises the experiences of Central and Eastern European regional cooperation and examines the basic nature of the cohesion problems of the Carpathian Basin trans-national macro region. It confirms by comparative historical analyses that the transformation was indeed unique. This book will make a welcome addition to the literature for students and academics interested in the broader picture of Central and Eastern European politics, future integration within the European Union and the history of regional development processes"--Resumé vydavatele